2012
DOI: 10.4172/2157-7099.1000163
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Histochemistry in Tumours of Colon, Ovaries and Lung

Abstract: Introduction: Mucins implicated in cancers of various organs. The apical epithelial surfaces of mammalian respiratory, gastrointestinal, and reproductive tracts are coated by mucus, a mixture of water, ions, glycoproteins, proteins, and lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Also, mucins constitute a major portion of the tumor area/volume in many cases . However, the rapid detection of mucin is challenging because current standard methods, like histochemical analysis of tumor tissues through PAS/Alcain blue staining, , are invasive and time-consuming and alternative approaches, such as enzyme-linked immunosorbent assays, antibody-mediated field-effect-transistor devices, and aptamer-based fluorometric assays, require expensive antibody-mediated reactions and complicated labeling steps for signal generation. Thereby, the development of a rapid “one-step” assay for analysis of mucins present in body fluids, tumor biopsy, etc., could enable integration to POC platforms for in vitro diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Also, mucins constitute a major portion of the tumor area/volume in many cases . However, the rapid detection of mucin is challenging because current standard methods, like histochemical analysis of tumor tissues through PAS/Alcain blue staining, , are invasive and time-consuming and alternative approaches, such as enzyme-linked immunosorbent assays, antibody-mediated field-effect-transistor devices, and aptamer-based fluorometric assays, require expensive antibody-mediated reactions and complicated labeling steps for signal generation. Thereby, the development of a rapid “one-step” assay for analysis of mucins present in body fluids, tumor biopsy, etc., could enable integration to POC platforms for in vitro diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Mucins are, therefore, an important factor in tumor cell survival and protection against the immune response of the affected host. An increase in mucin production has been observed in lung cancer [72], and secretory mucins act as a protective mechanism against exogenous cytotoxicity in tumor cells and increase the aggressiveness of a tumor [73]. Secretory mucins can cause web formations and heavily glycosylated membrane-bound mucins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, there is a tendency of increased production of sialomucins in various pathological conditions, with decreased O-acetylation as a common early feature of malignant and premalignant epithelial disorders, particularly in colon. This has been demonstrated both histochemically and biochemically in colorectal cancer, ulcerative colitis and in colonic adenoma 1,3,5,6 .…”
Section: Introductionmentioning
confidence: 90%
“…Expression of mucins is a property of epithelial cell types that exist in relatively harsh environments. Mucin's key characteristic is its ability to form gels; therefore they are a key component in most gel-like secretions, serving functions such as lubrication, cell signaling and forming chemical barriers 3 . In addition, mucins also communicate the information of the external environment to the epithelial cells via cellular signalling through membrane-anchored mucins.…”
Section: Introductionmentioning
confidence: 99%